Discovery : windows on the life sciences - Lewis, Ricki (Blackwell Science, 2001)
The goal of Discovery: Science as a Window to the World is to relay the excitement of sciene by exploring selected topics in biology and medicine in a way that reveals the process of discovery. Each chapter will focus on the curiosity and creativity that drives scientists to wonder, observe, question and experiment. One impetus for this project is the recognition of a growing demand among instructors for a book that departs from fact-stuffed textbooks and instead engages students in the discovery process at a personal level.:.; Emphasizes the process of discovery through interviews and key exp.